2010 IEEE Spoken Language Technology Workshop 2010
DOI: 10.1109/slt.2010.5700836
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of non-native speech using vowel space characteristics

Abstract: In this paper, we propose the idea of using the characteristics of a speaker's vowel space for automated assessment of second language (L2) proficiency. Specifically, we adpot features that were shown in previous studies to be good indicators of native speaker intelligibility and clarity and apply them to L2 speech from non-native speakers. The features focus on three peripheral vowels (IY, AA, and OW) and measure a speaker's coverage of the vowel space. A pilot study and a large-scale corpus study involving r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Several studies have shown that VSA is correlated with speech intelligibility, with larger values of VSA being associated with higher levels of intelligibility in normal native speech (de Boer, 2009; Neel, 2008; Smiljanić & Bradlow, 2009), normal non-native speech (Chen, Evanini, & Sun, 2010), and disordered speech (de Bruijn et al, 2009; Higgins & Hodge, 2002; Turner, Tjaden, & Weismer, 1995). VSA is only one factor that accounts for the intelligibility of speech, and its importance in any given speaker or group of speakers depends on other factors, such as the availability of different types of acoustic cues.…”
Section: 0 Derived Metrics and Data Displaysmentioning
confidence: 99%
“…Several studies have shown that VSA is correlated with speech intelligibility, with larger values of VSA being associated with higher levels of intelligibility in normal native speech (de Boer, 2009; Neel, 2008; Smiljanić & Bradlow, 2009), normal non-native speech (Chen, Evanini, & Sun, 2010), and disordered speech (de Bruijn et al, 2009; Higgins & Hodge, 2002; Turner, Tjaden, & Weismer, 1995). VSA is only one factor that accounts for the intelligibility of speech, and its importance in any given speaker or group of speakers depends on other factors, such as the availability of different types of acoustic cues.…”
Section: 0 Derived Metrics and Data Displaysmentioning
confidence: 99%
“…Intuitively, the speech dissimilarity between native and non-native speakers is much larger than among non-native speakers themselves. A study of vowel space characteristics between native and non-native speakers [8] provides support for this intuition. So it may be meaningful to use non-native speaker data to assess non-native speech.…”
Section: Introductionmentioning
confidence: 83%
“…We have presented the results of a study examining the utility of spectral features of vowels in the automated assessment of non-native English speech. Previous studies ( [9], [10]) have used vowel space size (or vowel dispersion) as a measure of accuracy in L2 pronunciation. However, the theoretical basis for this assumption remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies that have examined the use of formant characteristics in the automated assessment of speech intelligibility (e.g. [9]; [10]) have established a link between proficiency and vowel formant characteristics. It is regrettable, however, that no serious attempt has been made in the vast majority of these studies to normalise speaker differences in vocal tract sizes.…”
Section: Introductionmentioning
confidence: 99%